2010
DOI: 10.1007/s13364-010-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-male aggression in relation to female availability and residence status in corn mice Calomys musculinus

Abstract: We conducted an experimental study to test the hypothesis that, at low female availability, males show intrasexual aggressive behaviour and home range owners are more aggressive than home range intruders. Using field dyadic arena test, we carried out 35 male-male trials in four 0.25 ha enclosures, two male-biased (experimental enclosures) and two unbiased (control enclosures). Dyadic encounters were conducted between unrelated and sexually mature males of similar weight and age which established home ranges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Sommaro et al (2010b) found that C. musculinus females maintain their territories regardless of population density values and that at high population density they limit the size of the breeding population by constraining other females from settling. On the other hand, the upper limit in the number of C. musculinus breeding males is reached through induced territoriality derived from intrasexual social restrictions (Sommaro et al 2010b;Steinmann and Priotto 2011). Thus, C. musculinus spacing behavior would explain the similarity between multiple paternity rates at low and high population density found in this study.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Sommaro et al (2010b) found that C. musculinus females maintain their territories regardless of population density values and that at high population density they limit the size of the breeding population by constraining other females from settling. On the other hand, the upper limit in the number of C. musculinus breeding males is reached through induced territoriality derived from intrasexual social restrictions (Sommaro et al 2010b;Steinmann and Priotto 2011). Thus, C. musculinus spacing behavior would explain the similarity between multiple paternity rates at low and high population density found in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Before this study, C. musculinus promiscuity was assumed through behavioral characteristics of males and females in relation to space use, territoriality, mating, nesting, offspring guarding, and mate discrimination (Cutrera et al 1988;Yunes et al 1991;Laconi and Castro-Vázquez 1998;Laconi et al 2000;Steinmann et al 2009;Sommaro et al 2010b;Coda et al 2011;Steinmann and Priotto 2011). In the absence of paternal information, relatedness coefficients and paternity patterns among pups sharing a mother were inferred based on their genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Steinmann et al. ; Steinmann & Priotto ). In polygynous species, male aggressiveness leads to an increase in reproductive success by defending territories containing breeding females (Clutton‐Brock ; Shuster & Wade ; Waterman ); meanwhile, female territorial behaviour has been proposed as a strategy for defence of food resources (Hrdy ; Ims ; Ostfeld ; Tamarin et al.…”
Section: Introductionmentioning
confidence: 98%
“…A greater degree of imbalance in the OSR leads to a greater expected variance in reproductive success among members of the limited sex, affecting directly the degree of polygyny (Trivers 1972;Clutton-Brock and Parker 1992;Mitani et al 1996;Aloise King 2013). Many studies at the population level have revealed the impact of population density and OSR on spacing and mating behaviours of vole and mice (Ochiai and Susaki 2002;Steinmann et al 2006a, b;Stradiotto et al 2009;Sommaro et al 2010;Steinmann and Priotto 2011;Bonatto et al 2015;A ´vila et al 2016). For example, in some promiscuous and polygynous vole species, male home range size and overlap degree are negatively correlated with population density (Ostfeld et al 1985;Ostfeld 1986;Nelson 1995a, b;Bond and Wolff 1999;Moorhouse and Macdonald 2008;A ´vila et al 2016) and receptive female availability (Steinmann et al 2006a;Steinmann and Priotto 2011), while females maintain the size and exclusivity of its home ranges regardless of population density (Saitoh 1981;Ostfeld 1985;Erlinge et al 1990;Sommaro et al 2010;A ´vila et al 2016).…”
Section: Introductionmentioning
confidence: 99%